Decarbonizing the iron and steel industry: A systematic review of sociotechnical systems, technological innovations, and policy options. (July 2022) - Kim, Jinsoo; Sovacool, Benjamin K.; Bazilian, Morgan; Griffiths, Steve; Lee, Junghwan; Yang, Minyoung; Lee, Jordy
Abstract: The iron and steel industry is the largest coal consumer and the most greenhouse gas intensive industry. It consumes about 7% of global energy supply, and conservative estimates report that it is responsible for 7–9% of global greenhouse gas emissions. Decarbonization of the iron and steel industry is thus vital to meet climate change mitigation targets and achieve a sustainable future for the industry. This paper presents a comprehensive and systematic review that considered more than 1.6 million pieces of literature and analyzes in depth a shortlist of 271 studies on the iron and steel industry's decarbonization. Applying a sociotechnical lens that investigates raw materials, iron and steel making processes, steel products making and usage, and waste and recycling, the review identifies the climate footprint of the iron and steel industry. The review also assesses current and emerging practices for decarbonization, identifying 86 potentially transformative technologies. The benefits of decarbonizing the iron and steel industry are considered through energy and carbon savings, financial savings, and other environmental and public health benefits. Barriers to decarbonization are considered across financial, organizational, and behavioral aspects. The review also discusses various financial tools and policy instruments that can help overcome the barriers. Lastly, research gaps are outlined. Highlights: This review identifies carbon-intensive processes in the iron and steel industry. It discusses decarbonizing practices, innovations, and potential transformations. It examines the benefits to sector decarbonization as well as barriers. It discusses how financing, business models, and policy can be harnessed.